Impact of inadequate regulatory frameworks on the adoption of bio-fertilizer (eg PGPR) technologies: a case study of sub-Saharan Africa - Masso, C.; Jefwa, J.M.; Jemo, M.; Thuita, Moses N.; Tarus, D.; Vanlauwe, Bernard (Asian PGPR Society for Sustainable Agriculture, 2013)
Recently, there has been a lot of interest to promote bio-fertilizers for eco-efficient intensification of agricultural systems in sub-Saharan Africa (SSA). Bio-fertilizers are considered cost-effective and environmentally-friendly. In SSA, bio-fertilizers have not been sufficiently evaluated for quality and efficacy because of weak or absence of regulatory frameworks. Consequently, a proliferation of low quality and inefficacious bio-fertilizer products has been reported. Based on a stepwise assessment of 66 bio-fertilizer products found in Ethiopia, Kenya, and Nigeria in 2009-2011, in more than 90% of cases, product composition didn’t match indications on the product labels or label claims related to product benefits were not supported by our research results. A few products were however found very promising; for instance, Legumefix (a rhizobial inoculant for soybean) showed a benefit cost analysis > 2.5. There was an obvious need of discriminating high quality products from poor ones. A five year study (i.e. 2012-2017) has started aiming at addressing that gap and scaling-up the best promising bio-fertilizer products. One of the key outcomes of the new project is therefore the institutionalization of quality control and efficacy testing of bio-fertilizer products to virtually eliminate the proliferation of poor-quality and inefficacious ones. That will increase the confidence of smallholder farmers, with high risk aversion, in the bio-fertilizer technologies. Adoption of bio-fertilizers by the resource-poor smallholder farmers in SSA, the majority of the population, will certainly result in improved crop yields, food security, and consequently better livelihood.